2020
DOI: 10.3390/nu12061875
|View full text |Cite
|
Sign up to set email alerts
|

Development of Criteria for a Positive Front-of-Package Food Labeling: The Israeli Case

Abstract: Efforts to shape the food environment are aimed at reducing diet-related co-morbidities. Front-of-package labeling (FOPL) may support the consumers to make an informed decision at the point of purchase and encourage industry to reformulate food products. The Israeli Ministry of Health (MOH) implemented a unique FOPL system, using two colors: A mandatory warning (red) label alongside a voluntary positive (green) label. An independent Scientific Committee, from academia, the healthcare system, and MOH was appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
0
16
0
2
Order By: Relevance
“…In fact, an important policy step that may be useful in achieving this goal is implementation of Israel’s recent front-of-package labeling reform. Front-of-package labeling uses two colors: red to signify a mandatory warning and green (voluntary) to signify food that complies with national nutrition recommendations [ 19 , 29 ]. The new red/green labels are much easier for consumers to notice and read, hence potentially increasing consumers’ perceived confidence in understanding the information on nutrition labels and in turn encouraging them to purchase healthier products.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an important policy step that may be useful in achieving this goal is implementation of Israel’s recent front-of-package labeling reform. Front-of-package labeling uses two colors: red to signify a mandatory warning and green (voluntary) to signify food that complies with national nutrition recommendations [ 19 , 29 ]. The new red/green labels are much easier for consumers to notice and read, hence potentially increasing consumers’ perceived confidence in understanding the information on nutrition labels and in turn encouraging them to purchase healthier products.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to one triangle containing an exclamation point (to signal warning) [ 23 ], the box contained additional triangles(s) with text about excessive levels of a nutrient (EXCESS SUGARS) as well as an iconic depiction of the nutrient (e.g., the sugar label included a tablespoon of sugar). Similar to the current labeling system implemented in Israel [ 24 ], the final warning consisted of a black circle with the text high in added (nutrient) (e.g., HIGH IN ADDED SUGARS), with an iconic depiction in the center (e.g., the sugar label included cubes of sugar). For ease of reporting, hereafter we refer to each warning primarily by its shape (e.g., the octagon, triangle, or circle warning).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, some products are marked with a voluntary green label to indicate that their ingredients are on a list of healthier alternatives approved by the Ministry of Health. In fact, before the policy was enacted estimates indicated that 14.1% of food products from all food groups were eligible for negative FOP labels, 19.8% for positive FOP labels and 63.8% for no FOP labels at all [ 10 ]. The current study seeks to examine the impact of the new FOP labeling reform on consumers' decision-making regarding food purchases.…”
Section: Introductionmentioning
confidence: 99%